Fabrication of Cost-effective and Lithographically Patterned Flexible Paper Based Microfluidic Device Using Photo-PDMS for Point of Care Application. (2017) - Kare, Siva Prakasam O.; Das, Debanjan; Chaudhury, Koel; Das, Soumen
Abstract: We have developed a lithographically patterned flexible paper-based microfluidic device using photo polydimethylsiloxane (PDMS). Normal PDMS is converted into photosensitive PDMS with the desired photoinitiator. Further paper is lithographically patterned by photo PDMS to form hydrophobic region, where the flow of aqueous solution are restricted and a hydrophilic region, where fluids can flow by capillary action without any need of an external pump. The fabricated device can attain three-dimensional structured network flow on a single paper by repeated crease, without stacking multiple layers of individual paper.